Sara Paston-Williams: Traditional Puddings - Barker, Emma (Petits Propos Culinaires, 2024)
Sara Paston-Williams: Traditional Puddings: National Trust, 2002: ISBN 070780308X: 160 pp., index, h/b £10.99.